2017
DOI: 10.11606/0031-1049.2017.57.07
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Dendropsophus microcephalus and Scarthyla vigilans (Anura: Hylidae) at a locality in north-western Venezuela with notes on microhabitat occupation

Abstract: The coexistence of species with similar ecological requirements (food, space, time) Agelenidae (11.1%), Tachinidae (9.32%) and . Gryllidae (14.13%), Cicadidae (9.1%), Cicadellidae (8.3%) and Delphacidae (8.02%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Granted, other factors may have contributed to the difference between these studies, but it has been demonstrated that the level of taxonomic resolution can influence assumptions of prey utilization [ 34 ]. Dietary overlap appears substantially higher when the taxonomic resolution of prey is low and a decrease in overlap can be revealed with higher prey resolution [ 34 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Granted, other factors may have contributed to the difference between these studies, but it has been demonstrated that the level of taxonomic resolution can influence assumptions of prey utilization [ 34 ]. Dietary overlap appears substantially higher when the taxonomic resolution of prey is low and a decrease in overlap can be revealed with higher prey resolution [ 34 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that at the Order level, the overlapping is evident but not at higher levels of taxonomic resolution such as families or morphospecie. This classification reveals broadscale trophic patterns not detectable when working at a more detailed prey level, such as species or morphospecies (Piatti & Souza 2011, Fonseca-Pérez et al 2017. At a spatial scale, the sites were dissimilar in composition and abundance of species and morphospecies of prey.…”
Section: Spatial-seasonal Diets Dynamicsmentioning
confidence: 96%
“…Taking into account the high diversity of insects in tropical forests, no overlap is observed at higher taxonomic resolution levels such as family or morphospecies (García-Robledo et al 2020). These levels can be used to analyze diet variability locally and correctly identify the segregation of trophic niche, especially when the general pattern indicates overlap (Piatti & Souza 2011, Fonseca-Pérez et al 2017. The coexistence of species that have overlapping diets may be explained in part by the high abundance of the resource and by the segregation of prey at higher taxonomic resolution levels.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios del uso de microhábitats en anfibios brindan información importante acerca de los patrones de forrajeo y tipos de presas consumidas (Duré y Kehr, 2004;Cajade et al 2010;Posso-Peláez et al 2017). Se ha documentado que los anfibios adultos generalmente consumen invertebrados y en algunos casos pueden alimentarse de pequeños vertebrados, sin embargo, la composición taxonómica de las presas depende principalmente del patrón de uso de los microhábitats, dicha composición de las presas ha sido relacionada con el tamaño y sexo de los individuos (Fonseca-Pérez et al 2017). De acuerdo con Luría-Manzano et al (2018), la talla de las ranas es importante al momento de la captura de las presas, debido a que individuos de mayor tamaño consumen presas más grandes, en comparación con los más pequeños.…”
Section: Introductionunclassified